The threonine degradation pathway of the Trypanosoma brucei procyclic form: the main carbon source for lipid biosynthesis is under metabolic control. Issue 1 (25th August 2013) - Millerioux, Yoann; Ebikeme, Charles; Biran, Marc; Morand, Pauline; Bouyssou, Guillaume; Vincent, Isabel M.; Mazet, Muriel; Riviere, Loïc; Franconi, Jean‐Michel; Burchmore, Richard J. S.; Moreau, Patrick; Barrett, Michael P.; et al.
Summary The Trypanosoma brucei procyclic form resides within the digestive tract of its insect vector, where it exploits amino acids as carbon sources. Threonine is the amino acid most rapidly consumed by this parasite, however its role is poorly understood. Here, we show that the procyclic trypanosomes grown in rich medium only use glucose and threonine for lipid biosynthesis, with threonine's contribution being ∼ 2.5 times higher than that of glucose. A combination of reverse genetics and NMR analysis of excreted end‐products from threonine and glucose metabolism, shows that acetate, which feeds lipid biosynthesis, is also produced primarily from threonine. Interestingly, the first enzymatic step of the threonine degradation pathway, threonine dehydrogenase (TDH, EC 1.1.1.103), is under metabolic control and plays a key role in the rate of catabolism. Indeed, a trypanosome mutant deleted for the phosphoenolpyruvate decarboxylase gene (PEPCK, EC 4.1.1.49) shows a 1.7‐fold and twofold decrease of TDH protein level and activity, respectively, associated with a 1.8‐fold reduction in threonine‐derived acetate production. We conclude that TDH expression is under control and can be downregulated in response to metabolic perturbations, such as in the PEPCK mutant in which the glycolytic metabolic flux was redirected towards acetate production.